An audit of Dysphagia patients attending speech therapy clinic at a tertiary hospital in Malaysia - Amelia Inbam Neelagandan; Esther Tuin; Tay, Chia Yi; Rajesh Kumar Muniandy (Universiti Malaysia Sabah, 2021)
Swallowing involves 55 muscles, five cranial nerves and two cervical nerve roots. When the coordination of this reflex is disturbed, dysphagia occurs. Dysphagia refers either to the difficulty someone may have with the initial phases of a swallow or to the sensation that the foods or the liquids are being obstructed in their passage from the mouth to the stomach. The objective of the study was to identify the diagnosis of patients attending Speech Therapy clinic, in Queen Elizabeth Hospital, Kota Kinabalu, Sabah, and to identify the demography of dysphagic patients. From the 406 patients that came during the study period, 139 patients (34.2%) were diagnosed with dysphagia, followed by developmental language disorders (33.3%). Of the 139 patients diagnosed with dysphagia, most of them are within the 41 to 60 (43.2%) and above 60 (42.2%) age groups. The majority were males (66.2%). A total of 81 (58.3%) patients with dysphagia had a history of cerebrovascular accident. Dysphagia is a common disorder among patients attending Speech Therapy Clinics at Queen Elizabeth Hospital, Kota Kinabalu. Training of Speech Therapists and early dysphagia intervention leads to a better outcome.